It's not all about moral reasoning: Understanding the content of Moral Case Deliberation. (March 2018) - Svantesson, Mia; Silén, Marit; James, Inger
Background: Moral Case Deliberation is one form of clinical ethics support described as a facilitator-led collective moral reasoning by healthcare professionals on a concrete moral question connected to their practice. Evaluation research is needed, but, as human interaction is difficult to standardise, there is a need to capture the content beyond moral reasoning. This allows for a better understanding of Moral Case Deliberation, which may contribute to further development of valid outcome criteria and stimulate the normative discussion of what Moral Case Deliberation should contain. Objective: To explore and compare the content beyond moral reasoning in the dialogue in Moral Case Deliberation at Swedish workplaces. Methods: A mixed-methods approach was applied for analysing audio-recordings of 70 periodic Moral Case Deliberation meetings at 10 Swedish workplaces. Moral Case Deliberation facilitators and various healthcare professions participated, with registered nurses comprising the majority. Ethical considerations: No objection to the study was made by an Ethical Review Board. After oral and written information was provided, consent to be recorded was assumed by virtue of participation. Findings: Other than 'moral reasoning' (median (md): 45% of the spoken time), the Moral Case Deliberations consisted of 'reflections on the psychosocial work environment' to a varying extent (md: 29%). Additional content comprised 'assumptions about the patient's psychosocial situation' (md: 6%), 'facts about the patient's situation' (md: 5%), 'concrete problem-solving' (md: 6%) and 'process' (md: 3%). Conclusion: The findings suggest that a restorative function of staff's wellbeing in Moral Case Deliberation is needed, as this might contribute to good patient care. This supports outcome criteria of improved emotional support, which may include relief of moral distress. However, facilitators need a strategy for how to proceed from the participants' own emotional needs and to develop the use of their emotional knowing to focus on the ethically difficult patient situation.